PENINGKATAN ETIKA KERJA ISLAM TERHADAP KOMITMEN ORGANISASI DAN KEPUASAN KERJA (Studi Kasus Pada Staf Auditor Kantor Akuntan Publik Kota Semarang) - Alwiyah Alwiyah (Fakultas Ekonomi dan Bisnis Islam UIN Walisongo, 2016)
Today many organizations face a dynamic and changing environment which in turn requires the organization to adjust to the environment. Dynamic environments requires management to adopt changes regardless of work ethic (to modify the structure, objectives, technology, organization of work tasks, etc.) in order to adjust to the changing environment. Success in the field of employment is determined by various factors, such as the level of competence, professionalism and commitment to the field is practiced. Having regard to the Islamic work ethic and commitment to the organization hopefully someone can reach the level of job satisfaction. The purpose of this study to find empirical evidence of an increase in the work ethic of Islam against comitment affective, normative commitment, continuance commitment and job satisfaction. The population is a Staff Auditor who work on public accounting firm who are Muslims in the city of Semarang. Hypothesis testing using the F test, the coefficient of determination and t test, where the F test is used to determine the increase of Islamic work ethics to organizational commitment and job satisfaction. Coefficient of determination (R ²) was essentially measure how far the model's ability to explain the dependent variables. Determiasi value is zero and one. Value (R ²) is small means that the ability of the independent variables in explaining the dependent variable is very limited. T Test To test whether there is any significant relationship between dependent and independent variables.